Miss Julia rocks the cradle [large type] - Ross, Ann B. (Ross, Ann B. Miss Julia series., 2011)
Miss Julia has promised her husband, Sam, to mind her own business. What a relief! She doesn't have to spring into action when a dead body is found in a toolshed six blocks from her house. Instead, she can concentrate on what's really important-like figuring out who's been passing bad checks in her name and, most important, preparing for Hazel Marie's impending due date. Then again, who else can figure out why that awful Thurlow Jones is trying to cast suspicion on someone Miss Julia feels certain is innocent? And, after all, what Sam doesn't know won't hurt him, right? Miss Julia's investigative work on the possible murders-of her financial reputation and of the person in the toolshed-keeps her buzzing. But the sudden arrival of Hazel Marie's twins during a fierce blizzard brings a whole new set of challenges and a double helping of trouble for Ann B. Ross's indomitable southern heroine.